What is the role of the centre for educational scholarship? - Evans, P (Kathmandu University Medical Journal, 2010)
The role of the Centre for Educational Scholarship is to promote scholarship, in terms of teacher education, teacher accreditation, and teacher collaboration. The strategy adopted by the University of Glasgow, Scotland, UK, is outlined, and a way of estimating effectiveness is suggested. DOI: 10.3126/kumj.v7i3.2745 Kathmandu University Medical Journal (2009) Vol.7, No.3 Issue 27, 323-324